Genetic variation on chromosome 6 influences F cell levels in healthy individuals of African descent and HbF levels in sickle cell patients - Creary,LE; Ulug,P; Menzel,S; McKenzie,CA; Hanchard,NA; Taylor,V; Farrall,M; Forrester,TE; Thein,SL (PLoS ONE, 2009)
Fetal haemoglobin (HbF) is a major ameliorating factor in sickle cell disease. We investigated if a quantitative trait locus on chromosome 6q23 was significantly associated with HbF and F cell levels in individuals of African descent. Single nucleotide polymorphisms (SNPs) in a 24-kb intergenic region, 33-kb upstream of the HBS1L gene and 80-kb upstream of the MYB gene, were typed in 177 healthy Afro-Caribbean subjects (AC) of approximately 7% European admixture, 631 healthy Afro-Germans (AG, a group of African and German descendents located in rural Jamaica with about 20% European admixture), 87 West African and Afro-Caribbean individuals with sickle cell anaemia (HbSS), as well as 75 Northern Europeans, which served as a contrasting population. Association with a tag SNP for the locus was detected in all four groups (AC, P=0.005, AG, P=0.002, HbSS patients, P=0.019, Europeans, P=1.5×10¯). The association signal varied across the interval in the African-descended groups, while it is more uniform in Europeans. The 6q QTL for HbF traits is present in populations of African origin and is also acting in sickle cell anaemia patients. We have started to distinguish effects originating from European and African ancestral populations in our admixed study populations.